GERAKAN STOP ASIAN HATE: SEBUAH RESPONS RASISME TERHADAP KETURUNAN ASIA DI AMERIKA SERIKAT - Khairur Rizki; Ayu Putri Khairunnisa; Mahmuluddin (Indonesian Journal of International Relations, 2022)
This paper analyzes the response to racism experienced by Asian descent in the United States through the Stop Asian Hate movement. By using qualitative research methods and the use of critical race theory, it can be seen the various impacts of racism. This paper also uses the theory of new social movements which is elaborated with the concept of Connective Action to dissect the collective movements of society such as forming non-profit organizations, demonstrations, advocacy, and campaigns through digital media as an effort to protect Asian descendants in America. Racism against Asian descent in the United States continues to escalate even to the point of murder. Racism against Asian descent also experienced an increase in the era of President Donald Trump's leadership along with the spread of the Covid-19 Virus Pandemic in the United States in early 2020. Trump's racist personality has increasingly made hate crimes against Asian descent flourish